An implementation of variable step‐size least‐mean‐square based control algorithm for DSTATCOM. (11th December 2015) - Badoni, Manoj; Singh, Alka; Singh, Bhim
Summary: A number of power quality issues such as poor power factor, harmonics, and unbalancing of load occur commonly at the distribution level. These power quality problems can be alleviated using a three‐phase distribution static compensator (DSTATCOM). This paper presents the least mean square (LMS) based control algorithms for DSTATCOM for fixed and variable step sizes. Variable step‐size LMS (VSSLMS) based algorithm involves the calculation of weights corresponding to the fundamental components of active and reactive powers. These weights are utilized to estimate reference supply currents from distorted load currents. It is shown that VSSLMS‐based algorithm performs better than fixed step‐size LMS in terms of static error and convergence. It is also shown by simulation and experimental results that VSSLMS‐based algorithm provides satisfactory performance under various operating conditions such as dynamics of change in load and unbalancing. Copyright © 2015 John Wiley & Sons, Ltd.